2020
DOI: 10.1186/s12912-020-00504-z
|View full text |Cite
|
Sign up to set email alerts
|

Changing nursing practice within primary health care innovations: the case of advanced access model

Abstract: Background The advanced access (AA) model has attracted much interest across Canada and worldwide as a means of ensuring timely access to health care. While nurses contribute significantly to improving access in primary healthcare, little is known about the practice changes involved in this innovative model. This study explores the experience of nurse practitioners and registered nurses with implementation of the AA model, and identifies factors that facilitate or impede change. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 26 publications
(53 reference statements)
1
20
0
3
Order By: Relevance
“…Furthermore, there is little pre-registration clinical exposure to PHC settings for nurses and a lack of familiarity with the scope of PHC nursing practice ( Murray-Parahi et al, 2020 ). Ample evidence describes the important role nurses play in improving access to PHC and the quality of the care delivered ( Abou Malham et al, 2020 ). Two systematic reviews comparing primary care physicians with nurses reported nurses provided equal or better care, improved health outcomes, and higher levels of patient satisfaction for physical problems and chronic conditions ( Ansell et al., 2017 ; Laurant et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there is little pre-registration clinical exposure to PHC settings for nurses and a lack of familiarity with the scope of PHC nursing practice ( Murray-Parahi et al, 2020 ). Ample evidence describes the important role nurses play in improving access to PHC and the quality of the care delivered ( Abou Malham et al, 2020 ). Two systematic reviews comparing primary care physicians with nurses reported nurses provided equal or better care, improved health outcomes, and higher levels of patient satisfaction for physical problems and chronic conditions ( Ansell et al., 2017 ; Laurant et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…A Atenção Primária à Saúde é reconhecida como fundamental para o acesso universal aos serviços de saúde. No Brasil, um dos mecanismos de fortalecimento da Atenção Primária à Saúde é a Estratégia Saúde da Família, que se fundamenta na atenção à saúde de famílias com pessoas em condições crônicas na perspectiva da inclusão de ações individuais e coletivas de promoção à saúde, prevenção de doenças, diagnóstico, tratamento, reabilitação e redução de danos (23,24) .…”
Section: Discussionunclassified
“…Uygulamanın etkili ve hasta odaklı olmasını sağlamak, zamanında iyileştirme için kilit bir stratejidir. Hastaların ihtiyaçlarına uygun gelişmiş yenilikçi bir bakımı amaçlayan yenilikçi modeller oluşturulmalıdır (26).…”
Section: Discussionunclassified